Notícias de um tempo ausente: coletânea de textos sobre a perda - Ferreira, Bruno Abreu [UNESP]; Carneiro, Elisa Dias [UNESP]; Gomes, Giovana Valadares [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Este trabalho descreve o processo de planejamento, pesquisa e produção do livro de narrativas jornalístico-literárias “Notícias de um Tempo Ausente”: a fundamentação teórica e reflexões existenciais da temática da perda, assim como as estratégias, entrevistas e recursos utilizados para a inserção do ficcional no jornalismo nas narrativas apresentadas na coletânea.

This work describes the process of planning, research and production of a collection of journalistic-literary narratives called “Notícias de um Tempo Ausente” (“News from a Missing Time”): the theoretical basis and existential thoughts on the theme of “loss”, as well as strategies, interviews and resources used for the insertion of fictional techniques in journalism and in the narratives presented in the collection.
News from an absent time: a collection of texts about the loss
Keywords: Jornalismo; Jornalismo literário; Literatura; Perda; Morte; Journalism; New Journalism; Literature; Loss; Death